Staging women's lives in academia : gendered life stages in language and literature workplaces - Massé, Michelle A. (Michelle Annette), 1951-; Maglin, Nan Bauer (State University of New York Press, 2017)
"Argues that institutional change must accommodate women's professional and personal life stages. Staging Women's Lives in Academia demonstrates how ostensibly personal decisions are shaped by institutions and advocates for ways that workplaces, not women, must be changed. Addressing life stages ranging from graduate school through retirement, these essays represent a gamut of institutions and women who draw upon both personal experience and scholarly expertise. The contributors contemplate the slipperiness of the very categories we construct to explain the stages of life and ask key questions, such as what does it mean to be a graduate student at fifty? Or a full professor at thirty-five? The book explores the ways women in all stages of academia feel that they are always too young or too old, too attentive to work or too overly focused on family. By including the voices of those who leave, as well as those who stay, this collection signals the need to rebuild the house of academia so that women can have not only classrooms of their own but also lives of their own"--Provided by publisher.
Keywords: Women college teachers -- Professional relationships -- United States.; Women college teachers -- United States -- Social conditions.; Women in higher education -- Social conditions.; Women -- Education (Graduate) -- United States.; Women graduate students -- United States -- Social conditions.; Women college graduates -- Employment -- United States.; Professeures (Enseignement supérieur) -- États-Unis -- Conditions sociales.; Femmes dans l'enseignement supérieur -- Conditions sociales.; Femmes -- Enseignement des 2e et 3e cycles -- États-Unis.; EDUCATION -- Higher.; Women college graduates -- Employment; Women college teachers -- Social conditions; Women -- Education (Graduate); Women graduate students -- Social conditions; United States